Text-based Analysis of Keystroke Dynamics in User Authentication - Roy, Soumen; Roy, Utpal; Sinha, DD (International Journal of Computer Sciences and Engineering, 2015)
User Authentication process is the essential integral part of any secure or collaborative system. Where, Knowledge-based Authentication is convenient and low cost among currently used authentication processes. But, today, password or PIN is not limited in knowledge-based user authentication due to off-line guessing attacks; it demands higher level of security and performance together with low cost. Here, Keystroke Dynamics is the best possible solution, where the users are not only indentified by their password or PIN, their regular typing style is also accounted for. But this technique, as is now, suffers from accuracy level and performance. Thus, in order to realize this technique in practice a higher level of security and performance together with low cost version is demanded with an error to an accepted level. Hence, it is highly needed to identify the controlling parameters and optimize the accuracy and performance. In this paper we investigated typing style of 15 different individuals with 3 different texts and analyzed the collected data. Here, we introduced some effective factors which can optimize the accuracy and performance and at the end, we concluded by suggesting some future plans that also can be effectively implemented by this technique.